Method for improving comprehensive performance of PLA / PBS blended material by using compatilizer
By using reactive compatibility agents in PLA/PBS blended materials, the compatibility is improved, and the problem of insufficient mechanical properties of the blended materials is solved, and excellent mechanical properties, optical properties and full biodegradation ability are achieved.
Patent Information
- Application Number
- CN202411777618.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The poor compatibility of PLA/PBS blends leads to insufficient mechanical properties and impact resistance, limiting their application range.
Reactive compatibility agents, such as epoxidized soybean oil (ESO), triphenylmethane tetraisocyanate (DTTI), epoxy chain extender (REC), etc., are used to improve the compatibility between PLA and PBS through melt blending technology.
The mechanical properties, optical properties and processing properties of PLA/PBS blended materials are significantly improved, while reducing production costs and achieving the full biodegradation ability of the material.
Smart Images

Figure HDA0005171900450000011 
Figure HDA0005171900450000012 
Figure HDA0005171900450000021
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a polymer material, in particular to a method for improving the comprehensive performance of a PLA / PBS blended material by utilizing a compatibilizer. Background Art
[0002] Plastics are widely used in industrial production due to their excellent properties. However, the production and use of traditional petroleum-based plastics will generate a large amount of waste, which is currently mainly treated by incineration and landfill. Some of them even flow into the ocean, resulting in a low recycling rate. Under the general trend of sustainable development and environmentally friendly production, biodegradable materials are increasingly valued for their environmental friendliness.
[0003] Polylactic acid (PLA), as a biodegradable plastic, has attracted much attention due to its good biodegradability. It not only has good processing performance and biocompatibility, but also has high strength and modulus, with a tensile strength of up to 60MPa. However, PLA has a low glass transition temperature (60-65°C) and a low elongation at break at room temperature (usually less than 10%), showing greater brittleness and poor impact resistance, which limits its application range. Therefore, it can be modified by blending with other flexible copolymers.
[0004] Polybutylene succinate (PBS) is one of the most promising biodegradable polymers. As a "green" aliphatic polyester, PBS is not only biodegradable, but also easy to process, with good flexibility and mechanical properties, and can be used as a toughening agent for PLA. However, PLA and PBS have poor compatibility, resulting in a general modification effect. Therefore, in order to further improve the compatibility of PLA and PBS, the present invention adds a compatibilizer to improve the compatibility between PLA and PBS, and strengthens the bonding force between the interfaces of the two through a compatibilization reaction, thereby achieving a better modification effect.
[0005] The invention patent application with the patent number CN118222072A proposes a method for preparing a PLA / PBS heat-resistant biodegradable plastic. The invention prepares a compatibilizer by reacting tri(1-chloro-2-propyl) phosphate and epoxy propionic acid (GA) to improve the compatibility between PLA and PBS and the mechanical properties of the blend. However, its tensile strength drops from 52.8MPa to 37.3MPa.
[0006] Patent No. CN115785632A proposes a high-fluidity and high-toughness PLA / PBS blend alloy material and its preparation method. The method uses acetate to promote the transesterification reaction of PLA and PBS in the melt extrusion process of the compatibilizer, thereby obtaining an alloy compatibilizer containing a large amount of lactic acid-succinic acid-butanediol segments, thereby improving the fluidity of the final alloy product. However, this method has limitations in improving mechanical properties, and the elongation at break of the obtained blend system is only 20%.
[0007] Publication No. CN101724246A proposes a PBS / PLA / PHA biodegradable composite material and a preparation method thereof. The method improves the mechanical properties of the composite material by adding fillers, compatibilizers, plasticizers, antioxidants, antibacterial agents and other additives to the PBS / PLA / PHA blend. However, the method only increases the elongation at break to 110%, which is a small increase. Summary of the invention
[0008] The object of the present invention is to provide a method for improving the comprehensive performance of PLA / PBS blend materials by using a compatibilizer. The method adopts a reactive compatibilizer to improve the compatibility of PLA / PBS blends, thereby effectively enhancing the compatibility between PLA and PBS. The blend materials prepared by the method not only show excellent mechanical properties and optical properties, but also have good processing properties.
[0009] The objective of the present invention is achieved through the following technical solutions: A method for improving the comprehensive performance of a PLA / PBS blend material by using a compatibilizer, the method comprising the following steps: The dried PLA, PBS, compatibilizer, initiator and antioxidant were uniformly mixed and melt-blended in a twin-screw extruder. The temperature was set to 190°C, the rotor speed was set to 60 r / min, and the blending time was set to 6 min. The blended masterbatch was cut into several small pieces, cooled to room temperature and sealed.
[0010] The blended material comprises the following raw material components: Polylactic acid 60-90 parts; 10-40 parts of polybutylene succinate; Compatibilizer 0.5-3.5 parts; Initiator 0.1-0.15 parts; Antioxidant 0.1-0.5 parts.
[0011] The method for improving the comprehensive performance of a PLA / PBS blended material by using a compatibilizer, wherein the compatibilizer for the melt blending reaction is one or more of epoxidized soybean oil (ESO), triphenylmethane tetraisocyanate (DTTI), epoxy chain extender (REC), and polypropylene glycol sebacate (PPSC).
[0012] The method for improving the comprehensive performance of a PLA / PBS blended material by using a compatibilizer, wherein the initiator of the melt blending reaction is one or more of dibenzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), dicumyl peroxide (DCP), acrylamide (AM), and tert-butyl perbenzoate (TBPB).
[0013] The invention discloses a method for improving the comprehensive performance of a PLA / PBS blended material by using a compatibilizer. The antioxidant in the melt blending reaction is one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, N,N'-bis-(β-methyl-3,5-di-tert-butyl-4-hydroxyphenyl)oxalyl diimide, tris(nonylphenyl)phosphite and tris(2,4-di-tert-butylphenyl)phosphite.
[0014] The advantages and effects of the present invention are: The compatibilizer used in the present invention is safe and non-toxic. By introducing the compatibilizer, the interfacial force between PLA and PBS is increased, and the compatibility between the two phases is improved. In the experimental process, the addition of the compatibilizer can effectively improve the compatibility of PLA and PBS, so that the prepared blended material has excellent mechanical properties and optical properties while having complete degradation ability.
[0015] The raw material used in the present invention is a fully biodegradable material, which can effectively reduce the pollution of plastic waste to the environment and realize the sustainable utilization of resources. Meanwhile, the process designed by the present invention has significant advantages, and its simplicity, ease of implementation and strong operability bring great convenience to actual production. The whole process design is scientific and reasonable, without the need for complex equipment and high cost investment, and provides strong support for the innovative development of PLA / PBS composite materials in different fields, and widens its application field.
[0016] The present invention adopts a reactive compatibilizer, which can significantly improve the compatibility of the PLA / PBS blend, not only improving the rigidity and toughness of the material, but also further improving the mechanical properties, thermal properties and optical properties of the material. The required raw materials have low production costs, are safe and non-toxic, and have high production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a graph showing the effect of the amount of compatibilizer added on the impact strength of the PLA / PBS blend; Figure 2 . The effect of the amount of compatibilizer added on the tensile strength and elongation at break of PLA / PBS blends of the present invention; Figure 3 The effect of the amount of compatibilizer added on the thermal properties of PLA / PBS blends of the present invention is shown in (a) the heating curve; (b) the cooling curve; Figure 4 This is a graph showing the effect of the amount of compatibilizer added on the melt index and transmittance of the PLA / PBS blend. DETAILED DESCRIPTION
[0018] The present invention is described in detail below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments, and those skilled in the art can make some non-substantial improvements and adjustments to the present invention based on the contents of the above invention.
[0019] Embodiments 1-5 are embodiments of the present invention respectively, and the present invention will be described in detail below in conjunction with the embodiments.
[0020] Comparative Example 1 Polylactic acid: 80 parts Polybutylene succinate: 20 parts Initiator: 0.15 parts Antioxidant: 0.1 parts (1) The dried PLA, PBS, initiator and antioxidant were uniformly mixed and melt-blended in a twin-screw extruder. The temperature was set to 190 °C, the rotor speed was set to 60 r / min, and the blending time was set to 6 min. The blended masterbatch was cut into several small pieces, cooled to room temperature and sealed.
[0021] (2) The blend prepared in step (1) is molded into tensile specimens by a micro injection molding machine according to the national standard GB / T1040-1BA. The tensile properties of the molded specimens are tested; the blend prepared in step (1) is injection molded into impact specimens. The impact properties of the impact specimens are tested according to the national standard GB / T1843 / 1-A.
[0022] (3) The thermal properties of the blends were tested using differential scanning calorimetry (DSC) under a nitrogen atmosphere.
[0023] (4) The blend sample was pressed into a film with a thickness of about 80 μm using a flat vulcanizer, and the haze and transmittance of the blend film were tested using a haze meter.
[0024] (5) According to the test ASTM D1238-2013, the melt index of the blend was measured using a melt flow rate meter at 190 °C with a load of 2.16 kg. Example 1
[0025] Polylactic acid: 80 parts; Polybutylene succinate: 20 parts; Compatibilizer: 0.5 parts; Initiator: 0.15 parts; Antioxidant: 0.1 parts.
[0026] (1) The dried PLA and PBS were uniformly mixed with the compatibilizer, initiator and antioxidant, and melt-blended in a twin-screw extruder. The temperature was set to 190 °C, the rotor speed was set to 60 r / min, and the blending time was set to 6 min. The blended masterbatch was cut into several small pieces, cooled to room temperature and sealed.
[0027] (2) The blend prepared in step (1) is molded into tensile specimens by a micro injection molding machine according to the national standard GB / T1040-1BA. The tensile properties of the molded specimens are tested; the blend prepared in step (1) is injection molded into impact specimens. The impact properties of the impact specimens are tested according to the national standard GB / T1843 / 1-A.
[0028] (3) The thermal properties of the blends were tested using differential scanning calorimetry (DSC) under a nitrogen atmosphere.
[0029] (4) The blend sample was pressed into a film with a thickness of about 80 μm using a flat vulcanizer, and the haze and transmittance of the blend film were tested using a haze meter.
[0030] (5) According to the test ASTM D1238-2013, the melt index of the blend was measured using a melt flow rate meter at 190 °C with a load of 2.16 kg. Example 2
[0031] Polylactic acid: 80 parts Polybutylene succinate: 20 parts Compatibilizer: 1 part Initiator: 0.15 parts; Antioxidant: 0.1 parts.
[0032] (1) The dried PLA and PBS were uniformly mixed with the compatibilizer, initiator and antioxidant, and melt-blended in a twin-screw extruder. The temperature was set to 190 °C, the rotor speed was set to 60 r / min, and the blending time was set to 6 min. The blended masterbatch was cut into several small pieces, cooled to room temperature and sealed.
[0033] (2) The blend prepared in step (1) is molded into tensile specimens by a micro injection molding machine according to the national standard GB / T1040-1BA. The tensile properties of the molded specimens are tested; the blend prepared in step (1) is injection molded into impact specimens. The impact properties of the impact specimens are tested according to the national standard GB / T1843 / 1-A.
[0034] (3) The thermal properties of the blends were tested using differential scanning calorimetry (DSC) under a nitrogen atmosphere.
[0035] (4) The blend sample was pressed into a film with a thickness of about 80 μm using a flat vulcanizer, and the haze and transmittance of the blend film were tested using a haze meter.
[0036] (5) According to the test ASTM D1238-2013, the melt index of the blend was measured using a melt flow rate meter at 190 °C with a load of 2.16 kg. Example 3
[0037] Polylactic acid: 80 parts Polybutylene succinate: 20 parts Compatibilizer: 1.5 parts Initiator: 0.15 parts; Antioxidant: 0.1 parts.
[0038] (1) The dried PLA and PBS were uniformly mixed with the compatibilizer, initiator and antioxidant, and melt-blended in a twin-screw extruder. The temperature was set to 190 °C, the rotor speed was set to 60 r / min, and the blending time was set to 6 min. The blended masterbatch was cut into several small pieces, cooled to room temperature and sealed.
[0039] (2) The blend prepared in step (1) is molded into tensile specimens by a micro injection molding machine according to the national standard GB / T1040-1BA. The tensile properties of the molded specimens are tested; the blend prepared in step (1) is injection molded into impact specimens. The impact properties of the impact specimens are tested according to the national standard GB / T1843 / 1-A.
[0040] (3) The thermal properties of the blends were tested using differential scanning calorimetry (DSC) under a nitrogen atmosphere.
[0041] (4) The blend sample was pressed into a film with a thickness of about 80 μm using a flat vulcanizer, and the haze and transmittance of the blend film were tested using a haze meter.
[0042] (5) According to the test ASTM D1238-2013, the melt index of the blend was measured using a melt flow rate meter at 190 °C with a load of 2.16 kg. Example 4
[0043] Polylactic acid: 80 parts Polybutylene succinate: 20 parts Compatibilizer: 2 parts Initiator: 0.15 parts; Antioxidant: 0.1 parts.
[0044] (1) The dried PLA and PBS were uniformly mixed with the compatibilizer, initiator and antioxidant, and melt-blended in a twin-screw extruder. The temperature was set to 190 °C, the rotor speed was set to 60 r / min, and the blending time was set to 6 min. The blended masterbatch was cut into several small pieces, cooled to room temperature and sealed.
[0045] (2) The blend prepared in step (1) is molded into tensile specimens by a micro injection molding machine according to the national standard GB / T1040-1BA. The tensile properties of the molded specimens are tested; the blend prepared in step (1) is injection molded into impact specimens. The impact properties of the impact specimens are tested according to the national standard GB / T1843 / 1-A.
[0046] (3) The thermal properties of the blends were tested using differential scanning calorimetry (DSC) under a nitrogen atmosphere.
[0047] (4) The blend sample was pressed into a film with a thickness of about 80 μm using a flat vulcanizer, and the haze and transmittance of the blend film were tested using a haze meter.
[0048] (5) According to the test ASTM D1238-2013, the melt index of the blend was measured using a melt flow rate meter at 190 °C with a load of 2.16 kg. Example 5
[0049] Polylactic acid: 80 parts Polybutylene succinate: 20 parts Compatibilizer: 2.5 parts Initiator: 0.15 parts; Antioxidant: 0.1 parts.
[0050] (1) The dried PLA and PBS were uniformly mixed with the compatibilizer, initiator and antioxidant, and melt-blended in a twin-screw extruder. The temperature was set to 190 °C, the rotor speed was set to 60 r / min, and the blending time was set to 6 min. The blended masterbatch was cut into several small pieces, cooled to room temperature and sealed.
[0051] (2) The blend prepared in step (1) is molded into tensile specimens by a micro injection molding machine according to the national standard GB / T1040-1BA. The tensile properties of the molded specimens are tested; the blend prepared in step (1) is injection molded into impact specimens. The impact properties of the impact specimens are tested according to the national standard GB / T1843 / 1-A.
[0052] (3) The thermal properties of the blends were tested using differential scanning calorimetry (DSC) under a nitrogen atmosphere.
[0053] (4) The blend sample was pressed into a film with a thickness of about 80 μm using a flat vulcanizer, and the haze and transmittance of the blend film were tested using a haze meter.
[0054] (5) According to the test ASTM D1238-2013, the melt index of the blend was measured using a melt flow rate meter at 190 °C with a load of 2.16 kg.
[0055] The mechanical properties of the blend samples prepared in the comparative example and the embodiment were tested respectively; Figure 1 This is the effect of the amount of compatibilizer added on the impact strength of PLA / PBS blends; Figure 2 This is a graph showing the effect of the amount of compatibilizer added on the tensile strength and elongation at break of the PLA / PBS blend.
[0056] Table 1. Mechanical properties test results of composite materials Sample Elongation at break (%) Tensile strength (MPa) <![CDATA[Impact strength (J / m 2 ).]]> Comparative Example 1 109 48.94 3126.5 Example 1 125.47 55.71 6050.5 Example 2 156.38 55.34 6568.7 Example 3 234.26 56.46 7355.6 Example 4 234.15 57.03 7215.6 Example 5 230.59 56.31 6687.5 It can be seen from Table 1 that the impact strength and elongation at break of the blend without REC are 3126.5 J / m² and 109% respectively. When the addition amount of REC reaches 1.5 wt%, the impact strength reaches the optimal value of 7355.6 J / m², which is 2.35 times higher than that of Comparative Example 1; the elongation at break reaches 234.26%, which is 2.15 times higher than that of Comparative Example 1. At the same time, the impact strength increases slightly.
[0057] With the further increase of REC, the impact strength and elongation at break of PLA / PBS / REC blends slightly decreased to 7215.6 J / m² and 234.15%, respectively. From this analysis, it can be seen that excessive addition of REC will reduce the mechanical properties of the blend and weaken the toughening effect of PBS on PLA. This may be because when REC is excessive, the interface between PLA and PBS forms too strong adhesion, which limits the strain energy dissipation ability of the blend system. Therefore, when the addition amount of REC is 1.5 wt%, the mechanical properties of the PLA / PBS / REC blend system are optimal.
[0058] The thermal properties of the blend samples prepared in the comparative example and the embodiment were tested respectively. Figure 3 The effect of the amount of compatibilizer added on the thermal properties of PLA / PBS blends is shown in (a) the heating curve; (b) the cooling curve.
[0059] Table 2 Thermal properties test results of composite materials Sample <![CDATA[T m (PLA) / ℃]]> <![CDATA[T m (PBS) / ℃]]> <![CDATA[T g (PLA) / ℃]]> <![CDATA[T c (PBS) / ℃]]> Comparative Example 1 149.85 113.02 57.91 67.46 Example 1 147.92 112.58 58.02 62.14 Example 2 146.72 112.27 57.87 63.31 Example 3 146.55 111.94 57.78 67.30 Example 4 146.88 111.78 58.11 61.95 Example 5 146.74 111.46 58.65 64.62 according to Figure 3 From the test results in Table 2, it can be seen that the crystallization temperature of the PBS component in the PLA / PBS blend is 67.46°C. When 0.5 wt% REC is added to the PLA / PBS / REC blend, the crystallization temperature drops significantly to 62.14°C. However, with the further increase in the amount of REC added, the crystallization temperature of the PLA / PBS / REC blend gradually rises. This shows that at a higher amount of REC added, obvious heterogeneous nucleation occurs during the crystallization process of the blend, resulting in an advance in the crystallization temperature. The increase in the amount of REC added may enhance the compatibility of the blend, prompting the molecular chains of PLA and PBS to penetrate into each other's phase regions. With the improvement of compatibility, this enhancement effect becomes more obvious, thereby improving the crystallization point and crystallization efficiency.
[0060] The haze, transmittance and melt index of the blend samples prepared in the comparative example and the example were tested respectively. Figure 4 This is a graph showing the effect of the amount of compatibilizer added on the melt index and transmittance of the PLA / PBS blend.
[0061] Table 3. Melt index and transmittance of composite materials Test Name Comparative Example 1 Example 1 Example 2 Example 3 Example 4 Example 5 Transmittance / % 81.3 87.2 86.6 87.3 88.1 86.3 Melt index (g / 10min) 6.9 2.5 2.1 1.8 1.6 1.4 pass Figure 4 From Table 3, it can be found that compared with the pure PLA / PBS composite film, the melt index (MFR) of the blend is significantly reduced after adding REC. With the increase of REC addition, the MFR value decreases to a certain extent. When the REC addition is 0.5 wt%, the melt index of the PLA / PBS / REC blend reaches the minimum value of 2.5 (g / 10 min). This phenomenon shows that REC, as a small molecule additive, can promote the extension of the PLA / PBS molecular chain, thereby reducing the fluidity of the material. This also shows that with the addition of REC, the internal compatibility of the blend is improved through the compatibilization reaction, which ultimately manifests as a weakening of the fluidity of the material during extrusion. Figure 4It can also be found from Table 3 that with the increase of the amount of compatibilizer added, the transmittance always remains at around 87%. These results show that after the compatibilizer is introduced into the PLA / PBS blend system, the blend material maintains a high transmittance and exhibits good optical properties as a whole.
[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for improving the comprehensive performance of PLA / PBS blend materials by using a compatibilizer, characterized in that: The method comprises the following steps: The dried PLA and PBS were uniformly mixed with a compatibilizer, an initiator and an antioxidant, and melt-blended in a twin-screw extruder. The temperature was set to 190°C, the rotor speed was set to 60 r / min, and the blending time was set to 6 min. The blended masterbatch was cut into several small pieces, cooled to room temperature and sealed. The raw material components of the above PLA / PBS blended material are: Polylactic acid 60-90 parts; 10-40 parts of polybutylene succinate; Compatibilizer 0.5-3.5 parts; Initiator 0.1-0.15 parts; Antioxidant 0.1-0.5 parts.
2. A method for improving the comprehensive performance of PLA / PBS blend materials by using a compatibilizer according to claim 1, characterized in that: The compatibilizer for the melt blending reaction is one or more of epoxidized soybean oil (ESO), triphenylmethane tetraisocyanate (DTTI), epoxy chain extender (REC), and polypropylene glycol sebacate (PPSC).
3. A method for improving the comprehensive performance of PLA / PBS blend materials by using a compatibilizer according to claim 1, characterized in that: The initiator of the melt blending reaction is one or more of dibenzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), dicumyl peroxide (DCP), acrylamide (AM), and tert-butyl perbenzoate (TBPB).
4. A method for improving the comprehensive performance of PLA / PBS blend materials by using a compatibilizer according to claim 1, characterized in that: The antioxidant in the melt blending reaction is one or more of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, N,N'-bis-(β-methyl-3,5-di-tert-butyl-4-hydroxyphenyl) oxalyl diimide, tris(nonylphenyl) phosphite, and tris(2,4-di-tert-butylphenyl) phosphite.
Citation Information
Patent Citations
Blend of PPC, PLA, PCL and PBS and preparation method thereof
CN101724246A
High-fluidity and high-toughness PLA / PBS blending alloy material and preparation method thereof
CN115785632A
Stereo-composite interface compatibilized polylactic acid blending material and preparation method thereof
CN115028976A
Preparation method of bio-based auxiliary agent modified PLA / PBS composite material
CN117844205A
High-strength, high-toughness and high-heat-resistance injection molding foaming material and preparation method thereof
CN118206857A
Cited By
Plastic material for disposable tableware and preparation method thereof
CN121182166A